A Novel Transverse Flux Permanent Magnet Disk Wind Power Generator with H-Shaped Stator Cores - Guobin Peng (Energies, 2018)
This paper presents a novel transverse flux permanent magnet disk generator (TFPMDG) for wind power generation. The main features of its structure are the modular H-shaped stator cores and two simple rotor disks. What is different from the structures introduced in the references is that each H-shaped stator core is formed by two T-shaped iron cores and a permanent magnet (PM) rather than a complete H-shaped core, which makes the manufacturing simpler and easier. Each rotor disk consists of a rotor holder and several rotor bars, resulting in high robustness and reliability. Moreover, two circular coils in the H-shaped stator cores together with the stator disk are sandwiched by the two rotor disks, which improves the utilization of PMs. In this paper, the proposed TFPMDG is investigated in detail. Firstly, the structure and operating principle are introduced. Then, the magnetic circuit method is used to analyze the TFPMDG. Next, the three-dimensional (3D) finite element method (FEM) is employed to compute the magnetic field distribution and EMF at no load. According to the calculation result, the other three TFPMDGs with different shapes of rotor cores are proposed and analyzed for better back EMF, and then a generator with good performance is selected for load analysis. Finally, a prototype is fabricated and tested, and the simulated results are compared with the measured ones, which proves the rationality of the simulated results.